Implementation strategy for industrialised building system - Lim, Pui Chung (2006)
In Malaysia, the implementation of Industrialised Building System (IBS) by using precast concrete elements were introduced since 1966 when the government launched two pilot projects in 1966 which involves the construction of Tuanku Abdul Rahman Flats in Kuala Lumpur and the Rifle Range Road Flats in Penang. From the survey conducted by Construction Industry Development Board (CIDB) Malaysia, the level of usage of IBS in the local construction industry is 15% in 2003 although many government initiatives have been introduced to encourage the use of IBS. Therefore a study is conducted to study the current awareness of the usage of IBS in Malaysia. Furthermore this study will be conducted to analyse ways to improve the implementation of IBS in terms of the current policy and guideline available to implement the usage of IBS in the local construction industry. The study will be focused the usage of 50% of the IBS elements in terms of cost. The Strength, Weakness, Opportunity and Threat (SWOT) Matrix will be used to analyse the current scenario in the local construction industry and therefore the strategic implementation plan will be produced in this study.